PROBLEMATIKA PERNIKAHAN SIRI DI KECAMATAN PERAK KABUPATEN JOMBANG PADA ERA SOCIETY 5.0 - Fakhrurrozi, Azmirozi; Pradana, Sandi Yoga; Fauziyah, Ita Ma’rifatul; Saputro, Eko Andy (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
According to Islamic law, marriage is considered a very strong form of bond or mitsaqon ghalidhan to obey Allah's commands, and carrying it out is an act of worship. Siri marriage can be defined as